MULTI-WAVELENGTH OBSERVATIONS OF A LARGE SOLAR FLARE - Chornogor, S N.; Kondrashova, N. N. (Одеські астрономічні публікації, 2019)
We present the results of the multi- wavelength study of the two-ribbon solar flare on July 19, 2000 in the active region NOAA 9087. The evo- lution and morphological properties of the flare pro- ductive active region have been analyzed. The active region was growing rapidly and showed a complex mul- tipolar magnetic field configuration. It was large, pro- ducing many events, including the flare under consid- eration. The 3N/M6.4 two-ribbon flare was a promi- nent, long duration event in the active region evolution. According to Solar Geophysical Data (SGD) the flare lasted 2.5 hours. The flare energy release took place in many sites of the active region. We used combination of data from space and ground based observatories for study. The hard X-ray (HXR) and soft X-ray (SXR) data were obtained at the Yohkoh Telescopes (HXT and SXT) and Geostationary Operational Environmental Satellite (GOES). The full- disk magnetograms and EUV-images were provided by the Solar and Heliospheric Observatory (SOHO) Michelson Doppler Imager (MDI) and Extreme ultra- violet Imaging Telescope (EIT). We used the H α filter- grams from the Meudon spectroheliograph and white light images of Big Bear Solar Observatory (BBSO). All the data show continuously evolving SXR, EUV and H α features during the flare. The HXR and the type III radio bursts were observed at the flare onset. The first H α flare kernels and the surge, connected with the filament eruption, were initiated near a large positive-polarity sunspot. The main bright kernels of the flare occurred at the centre of the active region near magnetic neutral line, after that the flare ribbons appeared along it. It was found that HXR coronal source was located along a magnetic polarity inversion line of the active region. EUV loop structures indicate the observational evidence of a magnetic reconnection during the main phase of the flare.